Pengaruh Team Assisted Individualization Terhadap Motivasi Belajar Siswa Pada Pembelajaran Tematik - Fia Alifah Putri (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The purpose of this research is to know students learning motivation during the implementation of the Team Assested Individualization (TAI), ant then students learning motivation without using TAI, lasty, the influence of TAI to their motivation in thematic learning. The method used is a Quasi Experiment Research with the design of The Nonequivalent Pretest-Posttest Control Group Design, Non Probality sample with Purposive Sampling technique and analyzed using Independent Sample T-Test. Based on the results of the research can be summarized as follows, 1) The implementation of the TAI in thematic learning for teacher activities on average 96% and for student activities on averagec 83%. 2) Motivation of students with conventional learning models before learning by 54.59 and after learning by 58.43. 3) Motivation of students with the TAI learning model before learning by 54.49 in the high category and after learning by 65.31 in the very high category. 4) There is influence, with the Independent Sample T-Test of 0,000 smaller than the 0.05 sig. Where the experimental group amounted to 65.31 is influential than the control class amounted to 58.43.